Learning race, learning place : shaping racial identities and ideas in African American childhoods - Winkler, Erin N. (Rutgers series in childhood studies., 2012)
Erin N. Winkler uses in-depth interviews with an economically diverse group of African American children and their mothers to reorient the way we look at how children develop their ideas about race. She shows the importance of considering this process from children's points of view and listening to their interpretations of their experiences. The roles of gender, skin tone, colorblind rhetoric, peers, family, media, school, and, especially, place in developing children's racial identities and ideas are also examined.